Practice note on including children in spatial planning and design development processes - Ahmad, Peter. Chetty, Stefanie Mills. de Villiers, Inneke. Halligey, Alex. Harrison, Philip. Hobbs, Stephen. Kruger, Jill. Mayatula, Lekgolo. Swift, Melinda. (South African Research Chair in Spatial Analysis and City Planning, 2022)
There is much work required in Africa to bring the child’s voice into civic processes, and many contextual considerations to take account of, especially in relation to the poverty, vulnerability, and environmental deprivation of many children on the continent. There are some indications, however, of a growing awareness in places of the value of engaging children. By 2022, Child Friendly Cities Initiative programmes have been launched in Mozambique, Senegal, and Guinea, with involvement of UNICEF, national municipal networks, local universities, and civil society, with programmes in the process of setting up in Nigeria and Malawi. The Nairobi headquartered UN-Habitat has also supported child-responsive planning on the continent including through the Future Cities Challenge which encourages children to creatively re-imagine the cities they live in. In Southern Africa, Save the Children has undertaken a broad assessment of children’s participation across the region. South Africa has a National Plan of Action for Children in South Africa which was coordinated by the Department of Women, Children and People with Disabilities, and approved by Cabinet in 2013. It is an important document indicating South Africa’s acceptance of international treaties including the UN Convention of the Rights of the Child but does not address in detail the question of children’s participation in public policy and planning. However, the National Planning Commission, which prepared a National Development Plan (or NDP) in 2012, has launched an initiative called the Children’s NDP. This is an innovative initiative aimed at affirming children’s citizenship and agency. With its play-based experiential and learning method it has taken children through an engaging process of needs analysis and plan making, addressing the lived realities of children in South Africa. The case for children’s participation relates to all forms of future-oriented policy making and planning. This Practice Note however deals specifically with the children’s participation in spatial planning and design development processes that help shape the future form of our towns and cities and is targeted at government officials and private sector professionals in the built environment sector. The Note provides a bit of theory, an introduction to some precedent on engaging children, and some guidance on the process and content of child-friendly planning and design.